Exploring onco-fertility perceptions in India: a narrative review of psychosocial factors and implications for patients well-being - S., Ramya; Sheelam, Praveen K. (International Journal Of Community Medicine And Public Health, 2024)
Onco-fertility, the confluence of cancer and fertility preservation, is vital in modern healthcare. As global cancer survival rates rise, more patients aim to overcome cancer and safeguard their reproductive potential. This review explores onco-fertility in India, emphasizing psychosocial factors. It acknowledges cancer's profound implications on fertility, stressing informed decision-making and comprehensive care for dual challenges. The review explores various preservation options for both genders, highlighting India's evolving landscape. India's onco-fertility landscape, driven by rising cancer diagnoses and disparities, needs tailored services. Understanding psychosocial factors is crucial for addressing emotional distress, cultural contexts, and communication barriers. This review delves into factors influencing decisions and well-being, informing practices to better serve Indian cancer patients. Examining psychological distress and decision-making in balancing treatment and fertility preservation, it explores cultural, religious, and ethical considerations. It underscores the need for comprehensive psychosocial support. Addressing psychosocial factors is vital for enhancing cancer survivors' quality of life. The review emphasizes bridging information gaps, providing emotional support, promoting informed decision-making, and fostering collaboration. It calls for further research and initiatives to advance onco-fertility support, considering India's diverse psychosocial landscape.